Chapter Changes and Developments in the Linguistic Landscape of Present-Day Crimea - Bocale, Paola (Biblioteca di Studi Slavistici, 2016)
Following Crimea's incorporation into Russia in March 2014, the Crimean parliament adopted a new constitution granting official status to Russian, Ukrainian and Crimean Tatar. Despite the official multi-ethnicity and multilingualism of Crimea now constitutionally acknowledged, however, there is reason to believe that the formally proclaimed equality of the three languages has not translated into equality in practice. Among the areas where the inequality in language promotion and support is most noticeable, language education policy and language use in public place play a special role.